Liver clot after periodontal surgery: A rare case report - Aishwarya Virendra Satpute; Shailendra Singh Chaturvedi; Laxmikant Kashyap; Ravindra Soni; Sanghamitra Ghosh; Tarun Bhatnagar (Wolters Kluwer Medknow Publications, 2023)
Due to the primary closure of the fragile tissues, large postoperative drainage is unexpected following a periodontal medical procedure. This case study elaborately illustrates the formation of a "liver coagulation" or "currant jam clot" following a periodontal fold surgical operation. Contamination, internal damage, and the presence of foreign particles such as bone splinters or bits of dental restorative dressing can all increase the risk of an incident happening.